Endoscopic Full Thickness Resection for Gastrointestinal Tumors - Challenges and Solutions - Hung Leng Kaan; Khek Yu Ho (Korean Society of Gastrointestinal Endoscopy, 2020)
Standard polypectomy, endoscopic mucosal resection, and endoscopic submucosal dissection (ESD) are established techniques for the treatment of gastrointestinal tumors. However, resection of submucosal tumors via ESD often results in low rates of microscopically margin-negative (R0) resection and high rates of perforation. Endoscopic full thickness resection (EFTR) overcomes this adverse event and aids in the therapeutic management of complex tumors. Multiple techniques for EFTR have been developed, each with its own advantages and disadvantages. Submucosal tunneling and non-exposed techniques are generally preferable, because the layer of overlying intact mucosa reduces the incidence of intraperitoneal contamination by the gastric fluid and dissemination of the tumor cells. However, adoption of EFTR by endoscopists in clinical practice remains low. The major challenge seems to be the technical difficulty in performing laparoscopic and/or endoscopic suturing using the currently available instruments. We developed a novel robotic endoscopic platform with suturing capabilities to overcome the technical challenges of suturing. This platform allows easy maneuvering and triangulation of the instruments, thus facilitating endoscopic suturing using robotic arms. Our studies have demonstrated that this robotic endoscopic platform with suturing capabilities is an effective and safe method for performing EFTR with endoscopic suturing.